2011
DOI: 10.1002/mmce.20518
|View full text |Cite
|
Sign up to set email alerts
|

Design and simulation of a flexible beamforming interface for MIMO receivers using a Butler labyrinth

Abstract: This article focuses on the design and simulation of a new component for analog beamforming based on the Butler labyrinth. The proposed component enables the analysis of four-antenna beamforming in systems with two receive channels. The problem was to design a component that would enable simulation of a MIMO receiver with an accurate account of the analog beam-former effects on the digital signal processing level. The entire process is described-from layout design to the final DSP level integration and simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…is the most accurate compared to other methods. [5][6][7][8][9][10][11][12][13] As a key component for beamforming tracking, a switched beam system usually consists of an antenna array that can generate multiple fixed beams with enhanced precision. Beamforming tracking systems are known to be able to detect a target with high-range resolution when applied with ultra-wideband (UWB) methodology.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…is the most accurate compared to other methods. [5][6][7][8][9][10][11][12][13] As a key component for beamforming tracking, a switched beam system usually consists of an antenna array that can generate multiple fixed beams with enhanced precision. Beamforming tracking systems are known to be able to detect a target with high-range resolution when applied with ultra-wideband (UWB) methodology.…”
Section: Introductionmentioning
confidence: 99%
“…So far, several studies have been reported that deal with generating the line-of-sight pattern with a 3 Â 3 Butler matrix. 7,[10][11][12][13] In this article, a UWB 3 Â 3 modified Butler matrix built on a unique structure of Vivaldi antennas has been developed to overcome the problems such as diagnosis of a high-range resolution target, low gain in the whole UWB, line-of-sight pattern generation, and high SLL to achieve satisfactory beam-steering conditions. However, Vivaldi antennas that can operate at a bandwidth/center frequency ratio of more than 100% are subject to high SLLs when placed side by side in an arrangement of the array, as they will have a large size for the upper frequencies of the operating band.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations